Pemodelan Molekul Turunan p-Metoksi sinnamoil Hidrazida Sebagai Inhibitor Checkpoint Kinase 1 dan Inhibitor Aromatase secara In silico - Putra, Galih Satrio; Sulistyowatya, Melanny Ika; Ekowati, Juni; Budiati, Tutuk (UI Scholars Hub, 2018)
The development of anticancer drugs from ethyl p-methoxycinnamate (EPMC) derivatives has been done to compounds high activity in inducing cancer cells apoptosis and minimal side effects. p-Methoxycinnamoyl hydrazide derivates, modified from EPMC structure, were docked into the ligand-binding pocket of Check point kinase 1 enzymes (2YWP) and the aromatase enzyme (3S7S) using software Molegro Virtual Docker (MVD) Ver.5.5. We compared the Rerank score of native ligand with p-Methoxycinnamoyl hydrazide derivates. Rerank scores of compounds 4b and 4c (-99.98 Kcal/mol and -99.80 Kcal/mol) were lower than the native ligand A42 in inhibiting the enzyme checkpoint kinase 1. Rerank values of p-Methoxycinnamoyl hydrazide derivate compounds were greater than the native ligand EXM in inhibiting the enzyme aromatase. p-Methoxycinnamoyl hydrazide derivate compounds, especially compounds 4b and 4c, had anticancer mechanism by inhibiting the checkpoint kinase 1 enzyme pathway and showed no activity in inhibiting the aromatase enzyme.